2014
DOI: 10.1039/c4py01023j
|View full text |Cite
|
Sign up to set email alerts
|

Living polymerization of arylisocyanide initiated by the phenylethynyl palladium(ii) complex

Abstract: An air-stable phenylethynyl palladium(ii) complex was unexpectedly found to initiate the living polymerization of phenyl isocyanide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 26 publications
1
37
0
1
Order By: Relevance
“…The monomers M 1 (( R or S )‐decyl 2‐(4‐isocyanobenzamido)propanoate), M 2 ( tert ‐butyl 4‐isocyanobenzoate), trans ‐Pd(PEt 3 ) 2 Cl 2 , and polymer P1 ( M n = 28,364, M w / M n = 1.21) were synthesized according to the reported method . Potassium permanganate (KMnO 4 ), hydrochloric acid (HCl), 98% sulfuric acid (con.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The monomers M 1 (( R or S )‐decyl 2‐(4‐isocyanobenzamido)propanoate), M 2 ( tert ‐butyl 4‐isocyanobenzoate), trans ‐Pd(PEt 3 ) 2 Cl 2 , and polymer P1 ( M n = 28,364, M w / M n = 1.21) were synthesized according to the reported method . Potassium permanganate (KMnO 4 ), hydrochloric acid (HCl), 98% sulfuric acid (con.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, we developed a series of novel alkyne‐palladium(II) complexes which could promote the polymerization of various isocyanides in a living/controlled fashion, affording well‐defined polyisocyanides in high yields with controlled molecular weight ( M n s), narrow molecular weight distribution ( M w / M n s), and high stereoregularity . Using this family of versatile catalysts, a number of polyisocyanides with single‐handed helical sense can be facilely prepared .…”
Section: Introductionmentioning
confidence: 99%
“…Arylisocyanides have long attracted attention in the polymer community because of the propensity of materials formed from such monomers to form helical structures . The transition‐metal‐mediated controlled (co)polymerization of arylisocyanides is well‐documented, with complexes based on Ni II , Pt II , and certain dinuclear Pt II ‐Pd II species being particularly useful. In the context of this Minireview, we will highlight examples of Rh I ‐aryl complexes that have been shown to be effective in promoting the (co)polymerization of bulky arylisocyanides…”
Section: Rhodium(i)‐aryl Complexesmentioning
confidence: 99%
“…Nickel-catalyzed polymerization of isocyanides to helical polyimines is extensively reported in literature [11,12]. Recently, significant advances have been made in using palladium catalysis for similar transformations to polyimines [13][14][15][16][17][18]. Due to the nature of this transformation, affording polymeric structures rather than small molecules, these examples will not be treated in this review.…”
Section: Isocyanidesmentioning
confidence: 99%